The Method of Memorizing the Quran by Writing on a Lauhah (Board) - Fajriansyah, Bima; Abdurrahman, Muhammad Fathi; Yusuf, Muhammad Azmi; Syarifuddin, Amir (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Memorizing method using lauhah media Has often been applied in various African continent countries such as Sudan, Mauritania, Morocco, and others, of course, this method has shown its success, it can be seen that many students become huffadzul Quran produced through the lauhah or blackboard method, of course, this is the reason for the compiler to create a similar method which will later be adjusted to the conditions of students in Indonesia in its application, especially in educational institutions such as Islamic boarding schools and elementary schools to universities. This method uses a method board media, which will later be replaced with a special book to make it easier, the purpose of the book is to write the verses to be memorized, after the student writes, he will memorize the verse, after being memorized the student closes the book and submits the memorization to the ustaz or teacher, so it can be concluded that this method combines the ability to write and the ability to memorize, so that the student's memorization is very mutqin or strong. In the findings of the results of this learning method, we have found many students who are in khalwah (Islamic boarding schools)2 in Sudan, the students in their khalwah can memorize the Quran with very good quality, both in terms of reading and memorization strength, there is even a student who cannot see or is blind, but with his sincerity in studying and memorizing the Quran with the lauhah method applied, Alhamdulillah managed to memorize the thirty chapters of the Quran. Of course, something similar is something we can achieve. So with this lauhah method, it is hoped that it can be a solution for students to make it easier to memorize the Quran. However, apart from the method, teachers are also a very important element of success in achieving targets, with good guidance and support and the right facilities and methods, it will produce huffadzul Qur'an.